Analysis The Impact of E-Service Quality on E-Customer Satisfaction in Cinema Ticket Booking Application - Ditya Ilmi Rizqi; Utomo, Rio Guntur; Al Makky, Muhammad (School of Computing, Telkom University, 2023)
The development of technology and information has made everything easier and more efficient for us to obtain. One of its applications is online ticket booking in cinema networking applications. Innovations in the implementation of this technology can attract a significant number of buyers as it is considered to facilitate users in ticket booking transactions. Cinema networking service providers offer various features and information on their applications to attract buyers and create a positive image and trust for users to reuse their online cinema service applications. In order to maintain and enhance user satisfaction, service providers must also improve the quality of the services provided. This research aims to examine the influence of service quality on user satisfaction. Data collection was conducted through questionnaires distributed to respondents who are users of cinema ticket booking applications. The data processing technique used is SmartPLS (Smart Partial Least Squares) to analyze the measurement and structural models. The method employed is E-Service Quality with seven dimensions as indicators, namely Efficiency, Fulfillment, Reliability, Privacy, Responsiveness, Compensation, and Contact. The results of this study indicate the influence of E-Service Quality variables on E-Customer Satisfaction variables.